2020
DOI: 10.1055/a-1110-7508
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the Peripheral Nerves of the Forearm, Wrist and Hand: Definition of Landmarks, Anatomical Correlation and Clinical Implications

Abstract: Background Peripheral nerve pathologies of the upper extremity are increasingly assessed by high-resolution ultrasonography (HRUS), yet rapid identification of nerve segments can be difficult due to small nerve diameters and complex regional anatomy. We propose a landmark-based approach to speed up and facilitate evaluation and intervention in this region. Method Relevant landmarks and section planes for eleven nerve segments of the forearm, wrist and hand were defined by ultrasonography in cadaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…They reported that the cross-sectional area (disclosed as mean ± standard deviation) of the RN at the antecubital fossa was 9.3 ± 2.4 mm 2 , that of the MCN in the upper arm was 6.9 ± 2.5 mm 2 , and that of the vagal nerve was 5.0 ± 2.0 mm 2 . 21 Although a high-resolution US was capable of visualizing such small peripheral nerves, their anatomical landmarks in US scanning could further expedite their depictions as per Gruber et al 22 In the present study, the cutaneous nerve trunks localized proximal to the aneurysms were identified according to their landmarks in all patients. In contrast, it was difficult to visualize the peripheral branches that split from the trunks with few exceptions, because the thinner branches peripherally coursed away from the landmark superficial outflow veins.…”
Section: Discussionmentioning
confidence: 70%
“…They reported that the cross-sectional area (disclosed as mean ± standard deviation) of the RN at the antecubital fossa was 9.3 ± 2.4 mm 2 , that of the MCN in the upper arm was 6.9 ± 2.5 mm 2 , and that of the vagal nerve was 5.0 ± 2.0 mm 2 . 21 Although a high-resolution US was capable of visualizing such small peripheral nerves, their anatomical landmarks in US scanning could further expedite their depictions as per Gruber et al 22 In the present study, the cutaneous nerve trunks localized proximal to the aneurysms were identified according to their landmarks in all patients. In contrast, it was difficult to visualize the peripheral branches that split from the trunks with few exceptions, because the thinner branches peripherally coursed away from the landmark superficial outflow veins.…”
Section: Discussionmentioning
confidence: 70%
“…With the arm externally rotated the groove between the tendon of the flexor carpi radialis muscle and the tendon of the long palmar muscle (missing in 15–20 %) can be palpated. The probe is positioned axially at the distal third of the forearm 8 ( Fig. 9 ).…”
Section: Palmar Cutaneous Branch Of the Median Nervementioning
confidence: 99%
“…Bei nach außen gedrehtem Arm kann die Rinne zwischen der Sehne des Musculus flexor carpi radialis und der Sehne des Musculus palmaris longus (fehlt in 15–20 %) getastet werden. Der Schallkopf wird axial im distalen Drittel des Unterarms positioniert 8 ( Abb. 9 ).…”
Section: Ramus Palmaris Des Nervus Medianusunclassified
“…In general, the median nerve, the ulnar nerve, and the superficial branch of the radial nerve are easily visualized throughout their extent in the forearm ( 14 ) , as detailed in Table 1 and illustrated in Figure 1 . The deep branch of the radial nerve is also observed in its entirety relatively easy, although its identification between the heads of the supinator muscle can be impaired in cases of muscle hypertrophy, with reduction of the perineural fatty plane ( 3 , 15 ) .…”
Section: Technical Considerationsmentioning
confidence: 99%